Systemic sclerosis : an illustrated guide to manifestation and management in Asian skin - Palit, Aparna; Inamadar, Arun C. (New York, NY : CRC Press/Taylor & Francis Group, 2019)
This book presents a wide variety of cutaneous features of systemic sclerosis under one cover as cutaneous manifestations are often the first to appear and help in diagnosing this condition early. It has a multidisciplinary approach as systemic sclerosis is a multi-system disorder which comes under the purview of various medical specialties like dermatology, rheumatology and nephrology. Numerous cutaneous features are illustrated with explanatory notes. This book would help the students, teachers and professionals in identification, followed by subsequent treatment and management at an early stage. Key Features Focuses exclusively on systemic sclerosis Includes diagnostic tips Explores systemic sclerosis in dark skinned people Consists of key points at the end of each chapter Discusses diagnostic algorithms and flow charts
Systemic sclerosis : an overview / Aparna Palit, Arun C. Inamadar -- Pathogenesis / Ragunatha S. -- Classification and clinical features / Aparna Palit, Arun C. Inamadar -- Investigations & diagnosis / Arun C. Inamadar, Ajit B. Jangond -- Differenitial diagnoses of systemic sclerosis / Keshavmurthy A. Adya -- Management of scleroderma / Keshavmurthy A. Adya -- Scleroderma overlap syndromes / Akanksha Kaushik, Sendhil Kumaran N -- Childhood scleroderma / Muhammed Razmi T, Rahul Mahajan.
OCLC-licensed vendor bibliographic record.
Keywords: Systemic scleroderma; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; MEDICAL / General; MEDICAL / Dermatology; MEDICAL / Nephrology